Project management : the managerial process - Gray, Clifford F (McGraw-Hill Education, 2024)
Project Management: The Managerial Process is distinguished by its balanced treatment of both the technical and behavioral issues in project management as well as by its coverage of a broad range of industries to which project management principles can be applied. It focuses on how project management is integral to the organization as a whole. The text not only delivers the tools and processes is essential to successful project management but also an understanding that the effectiveness of these tools and methods are shaped and determined by the prevailing culture of the organization and interpersonal dynamics of the people involved.